Synergism of endophytic Bacillus subtilis and Klebsiella aerogenes modulates plant growth and bacoside biosynthesis in Bacopa monnieri - Shukla, Namita; Singh, Deepti; Tripathi, Arpita; Kumari, Poonam; Gupta, Rahul Kumar; Singh, Shiwangi; Shanker, Karuna; Singh, Akanksha (Frontiers in Plant Science, 2022)
Bacopa monnieri is the main source of pharmaceutically important bacosides; however, the low content of these molecules in planta remains a limiting factor for fulfilling the industrial requirement. The accumulation of secondary metabolites can be enhanced in plants upon inoculation with endophytes. In this study, we isolated and analyzed the culturable endophytes associated with different plant parts. By analyzing their impact on plant growth parameters (in vitro and in vivo) and Bacoside A content, we found few candidates which increased bacoside accumulation significantly. Finally, two promising endophytes namely Bacillus subtilis (OK070745) and Klebsiella aerogenes (OK070774) were co-cultivated with B. monnieri cuttings singly and in combination mode to clarify their effect on bacoside biosynthesis and their accumulation in B. monnieri shoot. Consortium-inoculated plants significantly enhanced the plant biomass and Bacoside A content with respect to single inoculation. The results of real-time quantitative (RT-PCR) revealed significant accumulation of bacoside biosynthetic pathway transcripts (HMGCR, PMVK, FDPS, SQS, and β-AS) in the case of plants inoculated with microbial combination, while the single inoculation of B. subtilis diverted the plant’s machinery toward the synthesis of phenylpropanoid genes like CCR, CAD, CHS, and HST. In addition, higher expression of MYB 2 and WRKY 1 transcription factors in combinational treatment points out their probable role in better physiological and developmental processes. Altogether, this is the first study on B. monnieri-endophyte interaction showing improvement in the accumulation of bacoside A by modulating various genes of metabolic pathway and thus suggests an effective “green approach” for augmenting in planta production of pharmaceutically important bacosides.